Preserving Rice Fields and Domestic Rice Adequacy: A Case Study in Banyumas Regency, Central Java, Indonesia - Bondansari; Widiatmaka; Machfud; Khursatul Munibah; Wiwin Ambarwulan (Journal of Natural Resources and Environmental Management)
The destruction of rice fields due to changes in their use in various regions of Indonesia affects the national food supply. In the long term, this phenomenon will threaten efforts to fulfill the adequacy of rice and increase the potential for a food crisis. This study analyzes the decline in domestic rice sufficiency due to destroying rice fields in the Banyumas Regency. This study was conducted using spatial modeling and the Micmac method. Respondents and experts were purposively determined based on the roles of 50 respondents and seven experts. The findings revealed that, on average, 103 hectares of rice fields in the Banyumas Regency were lost annually between 2007 and 2019. In 2045, it is estimated that the area of rice fields in Banyumas Regency will be 29,160 hectares, with a conversion rate from 2019 to 2045 of 1,384 hectares. Several driving factors are distance from the district capital, distance from roads, distance from settlements, distance from the irrigation channel, and population density. The essential factors influencing rice self-sufficiency include enforcing rice field preservation regulations, incentivizing measures for protecting rice fields, comprehensive spatial data on rice fields, sufficient access to irrigation water, proactive engagement of farmer collectives, and level of rice productivity.